DNA‐bound elastase of neutrophil extracellular traps degrades plasminogen, reduces plasmin formation, and decreases fibrinolysis: proof of concept in septic shock plasma. Issue 12 (4th November 2019) - Cruz, Dayana Barbosa da; Helms, Julie; Aquino, Lluvia Ramírez; Stiel, Laure; Cougourdan, Lucas; Broussard, Cedric; Chafey, Philippe; Riès‐Kautt, Madeleine; Meziani, Ferhat; Toti, Florence; Gaussem, Pascale; Anglés‐Cano, Eduardo
Abstract : Activation of platelets and neutrophils in septic shock results in the formation of microvascular clots containing an intricate scaffold of fibrin with neutrophil extracellular traps (NETs) DNA. NETs contain multiple components that might impact endogenous fibrinolysis, resulting in failure to lyse clots in the microcirculation and residual systemic microthrombosis. We propose herein that the reservoir of human neutrophil elastase (HNE) on NETs may directly interfere with the fibrinolytic mechanism via a plasminogen proteolytic pathway. To investigate this mechanism, we constructed fibrin‐NETs matrices by seeding and activating neutrophils onto a fibrin surface and monitored plasminogen activation or degradation. We demonstrate that the elastase activity of HNE‐DNA complexes is protected from inhibition by plasma antiproteases and sustains its ability to degrade plasminogen. Using mass spectrometry proteomic analysis, we identified plasminogen fragments composed of kringle (K) domains (K1+2+3, k1+2+3+4 ) and the serine protease (SP) region (K5 ‐SP). We further demonstrate that patients with septic shock with disseminated intravascular coagulation have circulating HNE‐DNA complexes, HNE‐derived plasminogen fragments, a low plasminogen concentration, and a reduced capacity to generate plasmin onto fibrin. In conclusion, we show that NETs bearing active HNE‐DNA complexes reduce plasminogen into fragments, thus impairing fibrinolysis by decreasing the local plasminogen concentration, plasminogen binding to fibrin, and localized plasmin formation.—Barbosa da Cruz, D., Helms, J., Aquino, L. R., Stiel, L., Cougourdan, L., Broussard, C., Chafey, P., Riès‐Kautt, M., Meziani, F., Toti, F., Gaussem, P., Anglés‐Cano, E. DNA‐bound elastase of neutrophil extracellular traps degrades plasminogen, reduces plasmin formation, and decreases fibrinolysis: proof of concept in septic shock plasma. FASEB J. 33, 14270‐14280 (2019). www.fasebj.org